Topical application of glycolic acid suppresses the UVB induced IL-6, IL-8, MCP-1 and COX-2 inflammation by modulating NF-κB signaling pathway in keratinocytes and mice skin. Issue 3 (June 2017) - Tang, Sheau-Chung; Liao, Pei-Yun; Hung, Sung-Jen; Ge, Jheng-Siang; Chen, Shiou-Mei; Lai, Ji-Ching; Hsiao, Yu-Ping; Yang, Jen-Hung
Graphical abstract: Highlights: Glycolic acid (GA) protects against UVB-induced inflammation by modulating NF-κB signaling pathways. 1–1.5% of GA is the most appropriate concentration for reducing inflammation in mouse skin. GA providing a safe and natural strategy for developing novel topical anti-inflammatory agents. Abstract: Background: Glycolic acid (GA), commonly present in fruits, has been used to treat dermatological diseases. Extensive exposure to solar ultraviolet B (UVB) irradiation plays a crucial role in the induction of skin inflammation. The development of photo prevention from natural materials represents an effective strategy for skin keratinocytes. Objective: The aim of this study was to investigate the molecular mechanisms underlying the glycolic acid (GA)-induced reduction of UVB-mediated inflammatory responses. Methods: We determined the effects of different concentrations of GA on the inflammatory response of human keratinocytes HaCaT cells and C57BL/6J mice dorsal skin. After GA was topically applied, HaCaT and mice skin were exposed to UVB irradiation. Results: GA reduced the production of UVB-induced nuclear factor kappa B (NF-κB)-dependent inflammatory mediators [interleukin (IL)-1β, IL-6, IL-8, cyclooxygenase (COX)-2, tumor necrosis factor-α, and monocyte chemoattractant protein (MCP-1)] at both mRNA and protein levels. GA inhibited the UVB-induced promoter activity of NF-κB in HaCaT cells. GA attenuated the elevation of senescence associated with β-galactosidase activity but did not affect the wound migration ability. The topical application of GA inhibited the genes expression of IL-1β, IL-6, IL-8, COX-2, and MCP-1 in UVB-exposed mouse skin. The mice to UVB irradiation after GA was topically applied for 9 consecutive days and reported that 1–1.5% of GA exerted anti-inflammatory effects on mouse skin. Conclusion: We clarified the molecular mechanism of GA protection against UVB-induced inflammation by modulating NF-κB signaling pathways and determined the optimal concentration of GA in mice skin exposed to UVB irradiation.